A Comparative Clinical Study to Evaluate the Efficacy of Panchasama Churna and Erand Paka in the Management of Amavata w.s.r. to Rheumatoid Arthritis - Singh, Jajbir (International Research Journal of Ayurveda & Yoga, 2024)
Background : Amavata (Rheumatoid arthritis) is one of the chronic diseases mainly affecting the joints with pain of severe degree being the main symptom with progressive destruction of the joints with crippling and deformities, arthritis poses an unavoidable clinical situation and prolonged morbidity warranting an active care. Ama and Vata are the two main pathognomic factors held responsible for causation of Amavata. Derangement of Agni that is Agnimandya is a chief factor responsible for the formation of Ama, which is main pathological entity of the disease. The etiological factor for both vitiation of Vata and formation of Ama are responsible for the manifestation of the disease Aim and Objectives: To evaluate and compare the effects of Panchasama Churna and Erand Paka in the Management of Amavata w.s.r. To Rheumatoid Arthritis. Materials and Methods : 30 patients of Amavata was selected from OPD and IPD of Lal Bahadur Shastri Mahila Ayurvedic College & Hospital, Bilaspur District Yamuna Nagar (Haryana) . Patient who was fulfilling the criteria for diagnosis and inclusion was included in this study irrespective of sex, caste, religion etc Result: Panchasama Churna i.e. Group A provided mild improvement in 100% of the patients after completion of treatment. Erand Paka i.e. Group B provided marked relief in 10% of the patients, moderate response in 30% of the patients and 60% of the patients were showed mild improvement. Combined effect of Panchasama churna and Erand Paka i.e. Group C provided marked relief in 10% of the patients, moderate response in 70% of the patients and 20% patients showed mild improvement after completion of the treatment. No patient got complete cure and was found unchanged/no response in all the groups.